Change of concentration of carbonic gas in blood of a person under the influence of electro-acoustic signals of nervous cells - M. T. Shaov; Z. A. Shaova; O. V. Pshikova (Юг России: экология, развитие, 2015)
In article cited the data on an opportunity of distant control by concentration of carbonic gas in arterial blood of a human with the help «the voices of neuron»